The Role of The Indonesian Insurance Mediation Body (BMAI) in Resolving Insurance Conflicts - Elyani, Elyani; Ida Nadirah; Maria Rosalina (Dinasti Research, 2024)
In this paper, we will review the regulation of insurance in Indonesia and the role played by the Indonesian Insurance Mediation Agency (BMAI) in resolving insurance-related conflicts. This research uses normative legal research methods. According to the definition of Soerjono Soekamto, method is a process, principles, and procedures for solving problems. This research is conducted through a careful, thorough, and comprehensive examination of certain phenomena with the aim of increasing human understanding. The regulation of the insurance industry in Indonesia is regulated by Law Number 40 of 2014 concerning Insurance, while Law Number 30 of 1999 regulates arbitration and alternative methods of conflict resolution. Differences of opinion between the parties involved are often the cause of conflicts in this context. The Indonesian Insurance Mediation Agency (BMAI) has been actively involved in resolving insurance conflicts since 2006. BMAI is a legal entity based on Pancasila and based on the 1945 Constitution, which operates independently and is neutral. BMAI plays a role in resolving conflicts, especially in the field of insurance in Indonesia through mediation, education, and arbitration processes.